Immigration controls the search for workable policies in Germany and the United States - Hailbronner, Kay; Martin, David A. 1948-; Motomura, Hiroshi 1935- (Berghahn Books, 1998)
Some of the most pressing questions in immigration law and policy today concern the problem of immigration controls. How are immigration laws administered, and how are they enforced against those who enter and remain in a receiving country without legal permission? Comparing the United States and Germany, two of the four extended essays in this volume concern enforcement; the other two address techniques for managing high-volume asylum systems in both countries.